Perkhidmatan pembaca, penggunaan bahan-bahan rujukan Malaysiana dan keperluan pembaca di perpustakaan undang-Undang - Sharipah Hanon, B. (Perpustakaan Universiti Malaya, 1985)
Reference service is one of the many services provided by the University of Malaya Law Library to its users. Owing to the special nature of Malaysian legal materials, readers often encounter difficulties in retrieving information, especially statutes, cases and articles published in journals. To assist retrieval, the Library indexes Malaysian Acts, Ordinances and subsidiary legislation, law reports and journals on cards. This article attempts to give the background and the usage of published and unpublished indexes.